PENGARUH PENERAPAN KAIZEN TERHADAP LABA USAHA PADA PT.ASTRA INTERNATIONAL TBK- TSO CABANG MANYAR GRESIK - tuharea, firdaus indrajaya (GEMA EKONOMI, 2020)
This research is a study that uses a quantitative approach. Data collection techniques are done by collecting questionnaires and company data. The respondents taken were the Service, Sales and Administration divisions. The research method taken is the multiple linear regression method. The results of this study concluded that the absence of the application of a significant effect between kaizen on operating income at PT. Astra International TBK - TSO Manyar Gresik Branch. But with the results of interviews with the cadre of the company, it states that the one that affects operating income for the company is the regional problem of the company's area. Although not influential, the application of the kaizen culture must always be cultivated to increase operating profit in the company PT. Astra International TBK - TSO Manyar Gresik.